2002
DOI: 10.1002/1521-3773(20021115)41:22<4313::aid-anie4313>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Alkylative Double Ring Opening of Epoxides: Synthesis of Enantioenriched Unsaturated Diols and Amino Alcohols

Abstract: Enantioselective generation and intermolecular trapping of a lithium carbenoid occurs in the reaction of epoxides of 2,5‐dihydrofuran, 2,5‐dihydropyrrole, and oxa‐ and aza‐bicyclo[n.2.1]alkenes (n=2, 3) with organolithium compounds in the presence of external chiral ligands. This methodology leads to the synthesis of important unsaturated diol and amino alcohol functionality (see scheme; tert‐butoxycarbonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, Hodgson et al have reported an alkylative double ring‐opening of dihydrofuran and dihydropyran epoxides with organolithium to give substituted alkenediols,58 and this reaction was also applied to dihydropyrroles and tetrahydropyridines to give substituted amino alcohols 59. When the reaction was performed in the presence of stoichiometric amounts of external chiral ligands, such as (–)‐sparteine ( 3 ) or bisoxazoline 7 , the corresponding double ring‐opened products were obtained with moderate enantioselectivities [24–43 % ee ; Equation (a) in Scheme ] 60…”
Section: Organometallic Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hodgson et al have reported an alkylative double ring‐opening of dihydrofuran and dihydropyran epoxides with organolithium to give substituted alkenediols,58 and this reaction was also applied to dihydropyrroles and tetrahydropyridines to give substituted amino alcohols 59. When the reaction was performed in the presence of stoichiometric amounts of external chiral ligands, such as (–)‐sparteine ( 3 ) or bisoxazoline 7 , the corresponding double ring‐opened products were obtained with moderate enantioselectivities [24–43 % ee ; Equation (a) in Scheme ] 60…”
Section: Organometallic Reagentsmentioning
confidence: 99%
“…It should be noted that the incorporation of the organometallic reagent occurs at a vinylic position, whereas the enantioselective ring‐opening of oxa‐ and azabicyclic compounds usually results in cycloalkenes bearing the nucleophile in an allylic position 61. This method is particularly valuable with tropane‐type meso epoxides because it provides a new and enantioselective access to substituted aminocycloheptenols [ n = 3; Equation (b) in Scheme ] 60,62. More recently, in a related approach, Hodgson et al have described an organolithium‐induced ring‐opening of N ‐ tert ‐butylsulfonyl (Bus)‐protected aziridines 8 in the presence of (–)‐sparteine ( 3 ) to give amino alcohol 9 , albeit with low yields and enantioselectivity (Scheme ) 63…”
Section: Organometallic Reagentsmentioning
confidence: 99%
“…In previous decades, the chiral ligand metal-based systems exemplified by Cr- and Co-salen , Zn-trialkanol amine, Ti- and LiGa-BINOL, and Sc-bipyridine have been among the most extensively applied for the desymmetrization of meso -epoxides with heteroatom-centered nucleophiles. More challenging ring openings have seen the use of chiral Lewis bases/SiCl 4 systems, including those involving carbon-centered nucleophiles , and stoichiometric chiral lithium bases that were used to obtain functionalized allylic alcohols. ,, …”
Section: Desymmetrization Of Meso-epoxidesmentioning
confidence: 99%